2016
DOI: 10.1111/acer.12941
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mammary Cancer Progression in Fetal Alcohol Exposed Rats by β‐Endorphin Neurons

Abstract: Background Fetal alcohol exposure (FAE) increases the susceptibility to carcinogen-induced mammary cancer progression in rodent models. Fetal alcohol exposer also have decreased β-endorphin (β-EP) level and caused hyperstress response, which leads to inhibition of immune function against cancer. Previous studies have shown that injection of nanosphere-attached dibutyryl cyclic adenosine monophosphate (dbcAMP) into the 3rd ventricle increases the number of BEP neurons in the hypothalamus. In this study, we asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…It is unclear if this complex interaction is involved in human FASD. However, it is interesting to note that individuals with Fanconi Anemia are predisposed to cancer due to DNA damage, predominantly due to reactive aldehydes, (Duxin and Walter, 2015) and rat models suggest that embryonic alcohol exposure may speed the acquisition of tumors (Polanco et al, 2010; Zhang et al, 2016). We know virtually nothing about the long-term health issues faced by individuals with FASD (Moore and Riley, 2015) and these findings may provide insight into these life long issues.…”
Section: Fasd Geneticsmentioning
confidence: 99%
“…It is unclear if this complex interaction is involved in human FASD. However, it is interesting to note that individuals with Fanconi Anemia are predisposed to cancer due to DNA damage, predominantly due to reactive aldehydes, (Duxin and Walter, 2015) and rat models suggest that embryonic alcohol exposure may speed the acquisition of tumors (Polanco et al, 2010; Zhang et al, 2016). We know virtually nothing about the long-term health issues faced by individuals with FASD (Moore and Riley, 2015) and these findings may provide insight into these life long issues.…”
Section: Fasd Geneticsmentioning
confidence: 99%
“…This set of studies underlines the importance of opioid antagonists pharmacokinetics and pharmacodynamics in their anti-cancer effects, and somewhat reconciles the previous findings that both agonists and antagonists offered protection, by suggesting that the antagonists increase the sensitivity to endogenous agonists that are actually protective. This is supported by the antineoplastic activity of β-endorphin shown in vivo in models of breast carcinogenesis ( 64 , 65 ), and antagonised by naloxone ( 64 ). Similarly, low dose naltrexone enhanced serum concentrations of beta-endorphin and met-enkephalin and survival rates in dogs with mammary carcinoma ( 66 ).…”
Section: Effect Of Opioid Antagonists On Tumour Growth and Metastasis: Preclinical Studies And Clinical Approachesmentioning
confidence: 84%
“…The elevated level of 5-HT in model rats is consistent with the TCM theory that "the pain is caused by obstruction." β-EP, as one of the main bodies of endogenous opioid peptides, is produced by the hypothalamus and pituitary in vertebrates during exercise, excitement, pain, consumption of spicy food, and orgasm, and it resembles opiates in its ability to produce analgesia and a feeling of well-being (Chang-Hui and Shi- Jia, 2012;Zhang et al, 2016). Many studies have confirmed its analgesic effect, and it has become recognized as an inhibitory neurotransmitter to adjust pain (Qun et al, 2012;Du et al, 2016).…”
Section: Discussionmentioning
confidence: 99%